Street food : exploring the world's most authentic tastes / Tom Kime - Kime, Tom
Recreate the world's most exciting snacks. Have you ever visited a bustling market abroad, discovered a freshly cooked, local delicacy, and thought 'I'd love to make that at home'? Tom Kime's world tour of fantastic food shows how to bring exotic flavours into your kitchen. Take your tastebuds on a global adventure and cook up 90 easy-to-follow recipes, from Chilean seafood empanadas to Moroccan hira bean soup. You can pick up local cooking tips and techniques, and follow inspirational ideas for mixing a variety of dishes including fritters, mezze, tapas and kebabs, so you can serve up a truly global street food experience.